Early screening of breast cancer recurrence by monitoring DNA methylation based biomarkers using semiconductor technology - Kalofonou,M; Toumazou,C (2014)
Breast cancer is one of the most common cancer types in women, with 1 in 8 women having a lifetime risk of incidence. From the cases of primary breast cancer, more than 30% of diagnosed and treated cases will most likely lead to a metastasis, also known as cancer recurrence, within a period of 5-15 years from time of first diagnosis, dependent on the aggressiveness and rate of disease progression. From the stage of first detection of primary breast cancer to the point of a metastatic recurrence, certain tumour-specific genetic and epigenetic changes occur. The use of epigenetic markers, specifically DNA methylation, as a biomarker for cancer has shown great potential due to its role in the initiation, progression and recurrence of the disease. Given that the time of the event of a metastasis can vary from the moment of initial diagnosis, the use of markers that could monitor tumour progression by detecting tumour-specific DNA methylation based changes would provide significant insight in estimating the risk of recurrence, so that the right therapy is being addressed at the right time, in a more personalised way. Current screening methods of breast cancer have shown that more newly developed/recurred breast cancer cases can now be diagnosed but with the risk of more false-positive findings which could further lead to unnecessary treatment due to the possible misinterpretation of the imaging result (low/high risk lesions). Studies have shown that DNA methylation patterns found in blood can be used as reliable markers for distinguishing breast cancer patients from healthy subjects as well as for assessing the progression of breast cancer after therapy. Detection of DNA methylation changes could therefore offer a very promising alternative approach to early screening of breast cancer recurrence, providing with a more individualised clinical assessment and management of cancer as a chronic disease. A Point-of-Care system using the methylation profile of carefully selecte